Genetic variation in populations from central Argentina based on mitochondrial and y chromosome DNA evidence - García, Angelina (2018)
We present new data and analysis on the genetic variation of contemporary inhabitants of central Argentina, including a total of 812 unrelated individuals from 20 populations. Our goal was to bring new elements for understanding micro-evolutionary and historical processes that generated the genetic diversity of the region, using molecular markers of uniparental inheritance (mitochondrial DNA and Y chromosome). Almost 76% of the individuals show mitochondrial lineages of American origin. The Native American haplogroups predominate in all surveyed localities, except in one. The larger presence of Eurasian maternal lineages were observed in the plains (Pampas) of the southeast, whereas the African lineages are more frequent in northern Córdoba. On the other hand, the analysis of 258 male samples reveals that 92% of them present Eurasian paternal lineages, 7% carry Native American haplogroups, and only 1% of the males show African lineages. The maternal lineages have high genetic diversity homogeneously distributed throughout central Argentina, probably as result of a recent common origin and sustained gene flow. Migratory events that occurred in colonial and recent times should have contributed to hiding any traces of differentiation that might have existed in the past. The analysis of paternal lineages showed also homogeneous distribution of the variation together with a drastic reduction of the native male population.